Lusophone Monumental Museum: intersecting ‘Africa’ and ‘Nation’ in identity discourses - Abadia, Lilia Rolim (2019)
The monumental museums that this thesis is concerned with are the ones with an acknowledged role in representing the nation, meaning that they take an important part in creating and mobilising specific national identity discourses. They are also institutions that in the 21st century face pressures to account for demands of social justice.